Early prenatal sonographic diagnosis of congenital hypophosphatasia - Tongsong T. (2014)
A pregnant woman of 14 weeks' gestation was sonographically examined due to large-for-dates uterine size. The ultrasound examination showed poor ossification of all bony structures. All limbs were shortened with no evidence of fractures. The echodensity approximated that of the surrounding organs. No acoustic shadowing was observed. Based on these sonographic findings, skeletal dysplasia and short-limb dwarfism were diagnosed, the most likely condition being congenital hypophosphatasia. Early cordocentesis was successfully performed at 15 weeks' gestation to determine fetal alkaline phosphatase concentration. This was undetectable. The prenatal diagnosis of congenital hypophosphatasia was made. After counselling, the woman decided to opt for termination of pregnancy which was performed vaginally. Post-abortion findings confirmed the prenatal diagnosis. To our knowledge, this is the earliest sonographic diagnosis of this condition reported.